Agroforestry is an option for mitigating the impacts of global warming - Newaj, Ram; Dhyani, S. K. (Indian Farming, 2015)
As the danger of climate change looms large on the environment, following agroforestry practice is one way to mitigate the negative effect of climate change. Agroforestry helps in sequestering carbon in their biomass, in the soil and in wood products. Although less carbon is stored per unit area in agroforestry systems, in comparison to the forests, but it allows the land to remain in use for the production of food or other crops. Since a large total land area is suitable for agroforestry practices, there is potential for large-scale carbon sequestration.